PROFESSIONAL IDENTITY CONSTRUCTION OF INDONESIAN EFL NOVICE TEACHERS: THE COVID-19 PANDEMIC CONTEXT - Devia Fitaloka, - (2023)
Teacher's professional identity is considered as one of the important aspects that influence the quality of teacher's teaching practice. However, research on EFL novice teachers' professional identity construction in Indonesia is understudied. The present study investigated the factors that contributed in shaping two EFL novice teachers' professional identities in Indonesia and how COVID-19 pandemic affected their identities as teachers. By employing a narrative-based case study, the data were collected through interviewing, online classroom observation, and documents, and were analyzed using Creswell's (2014) thematic analysis. The results of this study confirmed Yazan's (2018) theory that teachers' leaning, teachers' cognition, teachers' emotions, teachers' participation in community of practice, and contextual factors were found to be the most influential factors that shape the teachers' professional identities. Teachers' learning experiences served as the most significant factors in shaping their professional identities as their observation of former teachers during the learning experiences formed their imagined identity on how a teacher should be. In regards to COVID-19 pandemic, this study revealed that online teaching during the pandemic influenced the teachers as they became more creative, flexible, and adaptable. This study suggests that the educational stakeholders could provide supports and opportunities for teachers' learning and professional development, so that they could recognize the importance of teachers' professional identity in relation to their future profession as teachers.